O naszym hymnie narodowym - Kopczewski, Jan Stanislaw (Warszawa : Instytut Wydawniczy "Nasza Ksieg.", 1988)
A detailed history of the Polish national anthem.
Bibliography: p. [141].
Keywords: Wybicki, Jozef, -- 1747-1822.; Mazurek Dabrowskiego; National songs -- Poland -- History and criticism; Poland -- History -- 1795-1815.